Size-Segregated Particulate Mass and Carbonaceous Components in Roadside and Riverside Environments - Muhammad Amin (MDPI AG, 2021)
Air sampling for 12 h diurnal and nocturnal periods was conducted at two monitoring sites with different characteristics in Jambi City, Sumatra Island, Indonesia. The sampling was done at a roadside site and a riverside site from 2–9 August, and from 7–13 August in 2019, respectively. A cascade air sampler was used to obtain information on the status, characteristics and behavior of airborne particles with a particular focus on the ultrafine fraction (PM0.1). The number of light vehicles was best correlated with most PM size categories, while those of heavy vehicles and motorcycles with the 0.5–1 μm and with >10 μm for the nocturnal period, respectively. These findings suggest that there is a positive influence of traffic amount on the PM concentration. Using carbonaceous parameters related to heavy-vehicle emissions such as EC and soot-EC, HV emission was confirmed to account for the PM0.1 fraction more clearly in the roadside environment. The correlation between OC/EC and EC for 0.5–1 μm particles indicated that biomass burning has an influence on both in the diurnal period. A possible transboundary influence was shown as a shift in the PM0.1 fraction characteristic from “urban” to “biomass burning”.